La presencia del actor libertario en las luchas sociales en Argentina - Carlos Fos (Les Cahiers ALHIM)
In Argentina, theatre became a very efficient way of conveying Anarchist ideas, an ideology brought mainly from Europe by different inmigrant groups. This libertarian aesthetics was put into action by means of creative writing workshops as well as the staging of dramas and monologues where the influence of popular theatre forms was quite present.